Aplikasi Pembayaran Dompet Digital Mengguanakan Barcode QRIS di SMK Karya Guna 1 Bekasi - Aji Banyu; Amanda (ALMUISY: Journal of Al Muslim Information System, 2022)
Today's digital technology makes life in modern times very easy, especially the people's habit of making payments using cash in conducting transactions, especially in payment transactions for the student's Educational Development Contribution (SPP) fee. The problem that often occurs in SPP payment transactions is that students have to write down the data and nominal on the payment paper and students forget to bring their SPP card. In this research method used in data collection is the Waterfall method with the stages of analysis, design, implementation, testing and maintenance. This tuition payment system is implemented in a mobile application depth that is used for students to make tuition payment transactions to schools